Cultural Scripts and Multilingualism in the Sciences. - Foschi Albert, Marina (Glottodidactica, 2012)
The use of a reduced verbal system as ELF English as a lingua franca in the sciences does not appear to be a perfectly adequate way of expressing cultural identities. A modern society should instead enforce, through instruction, the understanding of several national cultural scripts, one’s own and others, and the understanding of the way communication and languages works. Multilingualism and interculture in the scientific world can be made possible by the digital world and its new editorial products.